Multibody Dynamics Formulation for Modeling and Simulation of Roller Chain Using Spatial Operator - Omar Mohamed (MATEC Web of Conferences, 2016)
This paper proposes a new approach for modeling and simulating roller-chain drives using multibody formulations. The presented approach models the chain links as spatial decoupled dynamic bodies. The chain links are modeled using two different dynamic representations for the pin-link and the bushing-link. The bushing-link is modeled with two descendent dynamic bodies to represent the rollers. The adjacent pin and bushing links are connected by compliant bushing force elements. An efficient search algorithm is used to detect the contact between the roller and the sprocket teeth while a nonlinear force module is used to predict the contact force. A generalized sprocket representation is used to model the sprocket. The spatial motion of the chain links allows the out-of-plane vibrational motion of the links as well as simulating sprockets misalignment. Using the compliant connection between links avoids using the iterative calculation needed to satisfy the joint constraint equations leading to more efficient calculation scheme. The nonlinear dynamic equations of motion are solved using recursive approach. Complex roller chains drives, bicycle chain and conveyance systems can be easily modeled and analyzed using the proposed approach.